The role of apoptosis inducing factor in the apoptosis of retinal pigment epithelium cells induced by oxidative stress - Fu, Y; Tang, M; Bai, L; Fan, Y (Cellular and Molecular Biology, 2016)
To explore the role of apoptosis inducing factor (AIF) in the apoptosis of retinal pigment epithelium (RPE) cells induced by oxidative stress. RPE cell apoptotic models were constructed by H2O2, Annexin V/PI flow cytometry and MTT assay were used to determine the changes of RPE cell apoptosis and proliferation. The production of reactive oxygen species (ROS) and mitochondrial membrane potential were observed. QRT-PCR and western blot were used to determine the expression of AIF to evaluate whether AIF-mediated non caspase pathway participated in the RPE cell apoptosis induced by H2O2. After adding melatonin, the production of ROS, RPE apoptotic rate and the changes of AIF expression were also detected. The production of ROS and apoptotic rate of RPE cells increased with the increase of H2O2 concentration and treating time. The expression of AIF increased evidently in cytoplasm, while not in mitochondria. After intervention with melatonin, the production of ROS was inhibited and the apoptotic rate decreased. However, the expression of AIF was not inhibited correspondingly. AIF may participate in but not be dominant in the process of RPE cell apoptosis induced by oxidative stress.